Experimental and Analytical Investigation Based on 1/2 Scale Model for a Cleanroom Unit Module Consisting of Steel Section and Reinforced Concrete - Sijun Kim; Se Woon Choi (Advances in Materials Science and Engineering)
The rapid advances in high tech industries and the increased demand for high precision and reliability of their production environments call for larger structures and higher vertical vibration performance for high technology facilities. Therefore, there is an urgent demand for structural design and vertical vibration evaluation technologies for high tech facility structures. For estimating the microvibration performance for a cleanroom unit module in high technology facilities, this study performs the scale modeling experiment and analytical validation. First, the 1/2 scale model (width 7500 mm, depth 7500 mm, and height 7250 mm) for a cleanroom unit module is manufactured based on a mass-based similitude law which does not require additional mass. The dynamic test using an impact hammer is conducted to obtain the transfer function of 1/2 scale model. The transfer function derived from the test is compared with the analytical results to calibrate the analytical model. It is found that, unlike for static analyses, the stiffness of embedded reinforcement must be considered for estimating microvibration responses. Finally, the similitude law used in this study is validated by comparing the full-scale analytical model and 1/2 scale analytical model for a cleanroom unit module.